Comparison of molecular methods for the detection of Eimeria in domestic chickens in Malaysia - Loo, Shu-San; Lim, Lik-Sin; Nurul-Ain Efendi,; Blake, Damer P.; Kawazu, Shin-ichiro; Wan, Kiew-Lian (Penerbit Universiti Kebangsaan Malaysia, 2019)
Coccidiosis, caused by the Eimeria species, greatly affects the poultry industry. Severity of the disease varies depending on the identity of the infecting parasites, encouraging identification of Eimeria species circulating on a farm as a valuable component of chicken management. Conventional methods of Eimeria species identification are time consuming and can be subjective in nature. Given these limitations, molecular approaches have been developed for specific detection of Eimeria species. In this study, faecal samples were collected from commercial broiler farms and subjected to microscopic examination for Eimeria occurrence. Eimeria species were putatively identified by morphological characterisation and grouped into three categories based on oocyst size. Molecular detection of Eimeria species occurrence in these samples was then performed using two published PCR assays (the individual components of a SCAR-based multiplex PCR, and assays developed for quantitative PCR, termed PCR-SCAR 1 and PCR-SCAR 2 here) and a LAMP assay. Comparison of the results obtained demonstrated that the three molecular methods were capable of detecting all Eimeria species of the reference Houghton strain, but showed varying efficiencies in detecting Malaysian field isolates. PCR-SCAR 2 was found to be the most effective, detecting all seven Eimeria species and indicating the presence of Eimeria parasites in most flocks. Differences in the ability of the molecular methods to detect Eimeria may be a consequence of sequence divergence between isolates from different regions, implying that development of region-specific methods using local Eimeria strains may be required to improve the efficiency of molecular assays for Eimeria detection.